Bioimpedance Analysis of Body Composition in Oncology Patients - Makhammatkulovich, Rakhimov Nodir; Shavkatovna, Shakhanova Shakhnoza; kizi, Madaminova Sevarakhon Mukhammadjon; Zafarovna, Kamolova Barno; Anarbayevich, Sharipov Farid (American Journal of Biology and Natural Sciences, 2025)
Relevance of the Study. The problem of nutritional disorders and sarcopenia in oncology patients has gained particular importance in recent years. Reduction of skeletal muscle mass and phase angle has been associated with decreased tolerance to anticancer therapy, higher rates of complications, reduced quality of life, and lower survival [Cruz-Jentoft et al., 2019; Paiva et al., 2010]. At the same time, the commonly used body mass index (BMI) does not reflect actual changes in body composition and cannot reliably detect sarcopenia, sarcopenic obesity, or hydration disorders [Norman et al., 2012].